Development and psychometric evaluation of a new patient -reported outcome measure for stroke self -management: The Southampton Stroke Self - Management Questionnaire (SSSMQ). Issue 1 (December 2015) - Boger, Emma; Hankins, Matthew; Demain, Sara; Latter, Susan
Abstract Background Self-management is important to the recovery and quality of life of people following stroke. Many interventions to support self-management following stroke have been developed, however to date no reliable and valid outcome measure exists to support their evaluation. This study outlines the development and preliminary investigation of the psychometric performance of a newly developed patient-reported outcome measure (PROM) of self-management competency following stroke; the Southampton Stroke Self-Management Questionnaire (SSSMQ). Methods A convenience sample of 87 people who had had a stroke completed responses to the SSSMQ, the Stroke Self-Efficacy Questionnaire and the Stroke Impact Scale. Scaling properties were assessed using Mokken Scale Analysis. Reliability and construct validity were assessed using intra-class correlation coefficient (ICC), Mokken and Cronbach's reliability coefficients and Spearman rank order correlations with relevant measures. Results Mokken scaling refined the SSSMQ to 28 scalable items. Internal consistency reliability (Mokkenr = 0.89) and test-retest reliability (ICC = 0.928) were excellent. Hypotheses of expected correlations with additional measures held, demonstrating good evidence for construct validity. Conclusions Early findings suggest the Southampton Stroke Self-Management Questionnaire is a reliable and valid scale of self-management competency. The SSSMQ represents a potentially valid PROM for the evaluation of self-management following stroke.